2019
DOI: 10.30682/nm1904h
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Economic Efficiency of Agricultural Enterprises in Turkey: A Dea Approach

Abstract: In this study, it is tried to determine the efficiencies of agricultural enterprises in the use of capital and credit in Turkey by DEA. In the scope of the study, 550 farmers in enterprises in Antalya, Konya, Karaman, Ankara, and Eskişehir were interviewed. According to the results of the data envelopment analysis, 95 farmers according to CRS, 134 according to under VRS, and 95 according to under SE were found to be effective. The higher average of the overall technical efficiency is Antalya (0.87) and Konya (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…They found that the efficiency of their production was low. The results obtained by Raheli et al [2] during their research applying the DEA method show that there were significant differences between efficient and inefficient farmers in the studied area. The main differences were in the use of chemical fertilizers, biocides and water for irrigation, i.e., better use of them would probably increase efficiency in the long term.…”
Section: Literature Reviewmentioning
confidence: 81%
“…They found that the efficiency of their production was low. The results obtained by Raheli et al [2] during their research applying the DEA method show that there were significant differences between efficient and inefficient farmers in the studied area. The main differences were in the use of chemical fertilizers, biocides and water for irrigation, i.e., better use of them would probably increase efficiency in the long term.…”
Section: Literature Reviewmentioning
confidence: 81%
“…DEA-based models have primarily been used for efficiency evaluation methods [15]- [17]. They are more inclusive of both input and output indicators and can simultaneously evaluate the efficiency of decision-making units (DMUs) with multiple inputs and outputs.…”
Section: B Buildup Of Modelsmentioning
confidence: 99%
“…While scholars have investigated TIE at the firm level, such as new energy vehicle enterprises (Fang et al, 2020), lithium‐ion battery listed enterprises (Zhong et al, 2022), or renewable energy enterprises (Shen et al, 2022), they paid little attention to TIE of agribusiness firms. In addition, although recent literature on agribusiness firms discusses economic efficiency (Aydin & Unakitan, 2018; Gunes & Guldal, 2019), nontechnological innovations (Fuentes & Soto, 2015), and total factor productivity (Nilsson, 2017), we are not aware of any empirical studies on agribusiness management that examine the impact of AD on TIE. Therefore, this merits further attention and investigation.…”
Section: Introductionmentioning
confidence: 99%